Influence of CAD/CAM Material and Preparation Design on the Long-term Fracture Resistance of Endocrowns Restoring Maxillary Premolars - Foad, Ahmed Mohsen; Hamdy, Amina; Abd el Fatah, Ghada; Aboelfadl, Ahmad (Brazilian Dental Science, 2020)
Objective: To evaluate the effect of different occlusal preparation designs and CAD/CAM materials on the fracture resistance of maxillary premolars endcrowns. Materials and Methods: sixty-four endodontically treated upper first premolars were randomly divided into four groups according to ceramic materials (Vita Enamic and IPS emax CAD) and occlusal preparation designs (Anatomical and horizontal butt joint). After teeth preparation, the restorations were all made by CAD/CAM system (Cerec MCXL). Half of each group had undergone cyclic fatigue testing of 105 cycles with 50N loading force at a frequency of 0.5Hz in a mechatronic chewing simulator machine, and then all samples were loaded to fracture using a universal testing machine with a cross head speed of 0.5mm/min recording the fracture resistance values in N . The specimens were measured and statistically analyzed using using three-way analyses of variance (ANOVA), followed by serial two-way and one-way ANOVAs at each level of the study. P-values were adjusted for multiple comparisons using BENFORRONI correction and the significance level was set at P ? 0.05 for all tests. Results: Vita Enamic endocrowns showed higher fracture resistance values than IPS e max specimens. Conclusions: Vita Enamic endocrowns with anatomical preparations were found to be more favourable restoring endodontically treated maxillary premolars. KEYWORDS Endocrowns; All-Ceramic; Fracture; Cyclic loading; CAD/CAM